Remedial effect of Sapindus saponaria extracts on a soil contaminated with diesel at laboratory level - Marín Velásquez, Tomás Darío (2021)
Two extracts of Sapindus saponaria were evaluated as remediators of a diesel contaminated soil, at laboratory level. The soil was contaminated with 100 ml of gasoil per kilogram and was treated with aqueous and hydroalcoholic extracts in doses of 50, 100 and 150 ml per kilogram of contaminated soil, with a control sample by natural attenuation. The design was randomized blocks with six treatments, a standard block, three replicates per treatment and a variable response (percentage of extractables with n-hexane, HEM), according to EPA 9071b. Samples were taken from each experimental unit at 15, 30 and 45 days and the HEM was determined. The statistical design was factorial ANOVA with multiple criteria of Student-Newman-Keuls and significance α = 0.05, to establish the influence of the experimental factors on the response variable. The extracts of S. saponaria had a positive effect, increasing the remediation efficiency, with respect to the control, in a statistically significant way, being the treatment with 150 ml of hydroalcoholic extract the most efficient with a removal of 93.9% of the gasoil, even when statistically there was no difference between the extracts and the factors that influenced were the amount of extract and the time of the test.